A Critical Analysis of the UAE Federal Decree-Law No.: (38) of 2021 on the Protection of Copyrights and Neighboring Rights - Khater, Nouri Hamad; Zaheeruddin, Mohammed (Journal of Ecohumanism, 2024)
Recently, by virtue of Federal Decree-Law No.: (38) of 2021, the United Arab Emirates has passed a new legislation for the protection of copyrights and neighboring rights; a legislation that is meant to replace the prior Copyrights and Neighboring Rights Law No.: (7) of 2002. In this regard, this new Decree-Law is consisted of Fifty-Three (53) Articles; hence, it is somewhat similar to the prior law, except for the addition of some new amendments for certain details as mentioned herein in this paper (e.g. Smart Applications are added to the list of Digital Works).For instance, pursuant to this new Decree-Law, it is now impermissible for the author to request cessation of the circulation of his digital works; and that is as an exception to his moral right to withdraw his work from circulation after its publication. In addition, this new Decree-Law has granted people with special needs the right to alter the published work, without prior permission of the author or his successor, so that those people may be capable of using those works in a way that is suitable to their conditions. Furthermore, the new Decree-Law has permitted the formation of a Grievances Committee at the Ministry of Economy, presided by a competent judge; and that is in order to hear all appeals submitted against decrees of the Ministry of Economy, concerning the rejection of works registration, the rejection of works’ transcription or translation for scientific purposes, or any other decrees issued by the ministry concerning copyrights and neighboring rights. In this sense, the executive regulation of this new Decree-Law has been issued under No.: (47) of 2022, including Twenty (20) Articles, duly covering the following aspects and procedures: a) the regulation of works’ collective management; b) the stated procedures for works registration; c) the legal actions concerning the financial rights of works; d) the stated procedures of mandatory licensing from the Ministry of Economy for the works’ transcription or translation for scientific purposes; and e) the stated procedures of appeal against decrees of the Ministry of Economy before the Grievances Committee. The object of research is to critically examine the similarity between the Federal Decree-Law No.: (38) of 2021 on the Copyrights and Neighboring Rights and the previous Law No.: (7) of 2002 on the Copyrights and Neighboring Rights, and to identify the new changes brought by the new legislation. The study reveals that the new law limits the right of the author, granted certain rights to the people with special needs, and provision for formation of the Grievance Committee. The study recommends for the unification of all legislations that relate to intellectual property, and create a separate provision for each type of intellectual property.